TINJAUAN LITERATUR : DESAIN KURIKULUM BERBASIS KOMPETENSI DAN EVALUASI HOLISTIK DI SEKOLAH DASAR - Lestari, Futry Ayu; Sari, Dea Puspita; Sukiman, Sukiman; Ananta, Muh. Rezky Alsyah (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to analyze the design of the Competency-Based Curriculum (CBC) and holistic evaluation methods in elementary schools, with a focus on implementation in Indonesia and lessons from global practices. The research employed a systematic literature review method, analyzing 25 sources published between 2010 and 2025, selected based on their relevance to CBC and holistic assessment. The sources included journal articles, books, and official reports accessed through Google Scholar, Scopus, and local repositories. Data were collected from written documents and analyzed using thematic coding techniques. The results show that CBC in elementary education is effective in integrating cognitive, affective, and psychomotor competencies through contextual and student-centered thematic approaches. Holistic evaluation methods, such as authentic and formative assessments, are more appropriate for elementary students compared to traditional testing systems. However, key challenges in implementation include limited teacher training, uneven infrastructure, restricted access to technology, and an education culture still focused on memorization. In conclusion, the successful implementation of CBC requires strong policy support, improved teacher capacity, technological integration, and stakeholder involvement to achieve inclusive and sustainable elementary education.